Retraction in Orthodontics – A Short Review - R. Vighnesh1, Ashith M.V2, Siddarth Shetty3, Supriya Nambiar4, Nidhin Philip Jose5, Shravan Shetty6 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim- The aim of this review is to discuss about the retraction mechanism in orthodontics and to discuss indetail regarding the mechanism of action and their application in orthodontics.Objective- To list out the difference types of retraction mechanics used and their merits and demeritsBackground- The basic principle of retraction mechanism can be used in orthodontic space closureinvolving retracing the canine initially followed by remaining anterior teeth or entire anterior teeth can beretracted at once using intra or extra oral anchorage. They are broadly classified into friction and frictionlessmechanism. Once the extraction of the teeth has been done, the orthodontist must choose the procedure toretract the teeth based on the demand of the case. This article provides the basic information of both themechanics and their application in orthodontics.Reason- This review mainly done for better assessment and benefits of retraction mechanics and itsappliances